2018
DOI: 10.3892/ijo.2018.4570
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying the effects of stress on tumorigenesis and metastasis (Review)

Abstract: Stress is one of the fundamental survival mechanisms in nature. Although chronic or long-lasting stress can be detrimental to health, acute or short-term stress can have health benefits. The aim of the present review was to address the complexity and significance of stress in tumorigenesis. The review covers an evaluation of previously used and reported experimental animal models of stress, as well as the effects of stress on the neuroendocrine system, immune function, gut microbiota, and inflammation and mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 137 publications
(132 reference statements)
1
10
0
Order By: Relevance
“…The information on PSA concentration dynamics before treatment was available for about 2,500 of the cases included in the database, making it possible to determine the doubling time of PSA concentration (PSADT) that allows assessing tumor growth rate and aggressivity, serving as a valuable prognostic criterion [23][24][25]. It is also remarkable that the psychological state of the PC patients included in the database appeared to correlate with the PSADT and disease prognosis [27], thus corroborating observations of other authors mentioned before [11][12][13][14][15][16][17][18].…”
Section: Introductionsupporting
confidence: 77%
See 3 more Smart Citations
“…The information on PSA concentration dynamics before treatment was available for about 2,500 of the cases included in the database, making it possible to determine the doubling time of PSA concentration (PSADT) that allows assessing tumor growth rate and aggressivity, serving as a valuable prognostic criterion [23][24][25]. It is also remarkable that the psychological state of the PC patients included in the database appeared to correlate with the PSADT and disease prognosis [27], thus corroborating observations of other authors mentioned before [11][12][13][14][15][16][17][18].…”
Section: Introductionsupporting
confidence: 77%
“…Oncological conditions are known to occur less frequently in schizophrenia patients [11,[13][14][15][16], and this phenomenon primarily affects men [50], being especially pronounced for PC [13,[16][17][18]. Interestingly, PC has recently emerged as a cancer, development of which strongly depends on neurogenic regulatory pathways provided by nerves growing as an important TME component [51].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies indicated that an excess of ROS/RNS followed by OS, i.e., a disturbance of equilibrium between prooxidant processes and the protective strategies of antioxidant defense system, is genotoxic and can induce DNA damage; thus, they may play a key role in cancer development and progression [75, 77, 78] and in neuropsychiatric disorders, such as schizophrenia or depression [108]. Excess intracellular ROS may result in neuronal membrane damage, alter a broad range of its functions, and cause multineurotransmitters' pathologies [69].…”
Section: Discussionmentioning
confidence: 99%